Decreasing Shortest Path Length of the Sensorimotor Network Induces Frontal Glioma-Related Epilepsy - Fang, Shengyu; Li, Lianwang; Weng, Shimeng; Guo, Yuhao; Zhang, Zhong; Wang, Lei; Fan, Xing; Wang, Yinyan; Jiang, Tao (Frontiers in Oncology, 2022)
Background: Glioma-related epilepsy (GRE) is a common symptom in patients with prefrontal glioma. Epilepsy onset is associated with functional network alterations. This study investigated alterations of functional networks in patients with prefrontal glioma and GRE. Methods: Sixty-five patients with prefrontal lobe gliomas were retrospectively assessed and classified into GRE and non-GRE groups. Additionally, 25 healthy participants were enrolled after matching for general information. Imaging data were acquired within 72 hours in pre-operation. The sensorimotor network was used to delineate alterations in functional connectivity (FC) and topological properties. One-way analysis of variance and post-hoc analysis with Bonferroni correction were used to calculate differences of FC and topological properties. Results: All significant alterations were solely found in the sensorimotor network. Irrespective of gliomas located in left or right prefrontal lobes, the edge between medial Brodmann area 6 and caudal ventrolateral Brodmann area 6 decreased FC in the GRE group compared with non-GRE group (p < 0.0001 [left glioma], p = 0.0002 [right glioma]). Moreover, the shortest path length decreasing were found in the GRE group compared with non-GRE group (p = 0.0292 [left glioma] and p = 0.0129 [right glioma]). Conclusions: The reduction of FC between the medial BA 6 (supplementary motor area) and caudal ventrolateral BA 6 in the ipsilateral hemisphere, and shortening the path length of the sensorimotor network were characteristics alterations in patients with GRE onset. These findings fill in the gap that the relationship between GRE onset and the alterations of functional network in patients with prefrontal glioma.